The haemocytes of the colonial aplousobranch ascidian Diplosoma listerianum: Structural, cytochemical and functional analyses. (November 2017) - Cima, Francesca; Peronato, Anna; Ballarin, Loriano
Highlights: This is the first characterisation of haemocytes in an aplousobranch ascidian. A series of microscopic techniques modified for invertebrate tissues is presented. Behaviour and changes of haemocytes have been observed after experimental stimuli. Eight morphotypes are described at both light and electron microscopy. A comparative analysis with haemocytes of other ascidian orders is discussed. Abstract: Diplosoma listerianum is a colonial aplousobranch ascidian of the family Didemnidae that is native to the northeast Atlantic and exhibits a cosmopolitan distribution in temperate waters. It lacks a shared colonial circulation crossing the tunic, and the zooids are connected only by the common tunic. In the present study, the haemocytes of this ascidian were analysed via light and electron microscopy. Their phagocytic and enzymatic activities, staining and immunostaining properties, and lectin affinity were examined with various classical methods reconsidered and modified for small marine invertebrates. Eight morphotypes were identified in reference to corresponding cell types described in other ascidians: undifferentiated cells (haemoblasts), storage cells for nitrogenous catabolites (nephrocytes) and immunocytes. The immunocytes are involved in immune responses, acting as (1) phagocytes, rich in hydrolases and involved in the clearance of both foreign particles and effete cells (hyaline amoebocytes and macrophage-like cells); (2) cytotoxic cells, able to degranulate and induce cytotoxicity through the release of the enzyme phenoloxidase after an immune stimulus (granular amoebocytes and morula cells); and (3) basophilic cells with an affinity for ConA and NPA that contain heparin and histamine and that show sensitivity to the compound 48/80, promoting their degranulation (mast cell-like granulocytes). In addition, a particular cell type showing exceptional development of the Golgi apparatus and large vacuoles containing a filamentous material has been recognised (spherule cell), for which a role in tunic repair and fibrogenesis has been hypothesised.